Molecular dynamics of Middle East Respiratory Syndrome Coronavirus (MERS CoV) fusion heptad repeat trimers. (August 2018) - Kandeel, Mahmoud; Al-Taher, Abdulla; Li, Huifang; Schwingenschlogl, Udo; Al-Nazawi, Mohamed
Graphical abstract: Highlights: Virus-membrane fusion proteins have vital role in MERS CoV replication. Both trimers and monomers were found in both of virus and cell membranes. Changes in MERS CoV heptad repeat domains monomers and trimers were resolved by MD simulation. Monomer was unstable, having high RMSDs with major drifts above 8 Å. Trimer is more dynamically stable with very low RMSD. Abstract: Structural studies related to Middle East Respiratory Syndrome Coronavirus (MERS CoV) infection process are so limited. In this study, molecular dynamics (MD) simulations were carried out to unravel changes in the MERS CoV heptad repeat domains (HRs) and factors affecting fusion state HR stability. Results indicated that HR trimer is more rapidly stabilized, having stable system energy and lower root mean square deviations (RMSDs). While trimers were the predominant active form of CoVs HRs, monomers were also discovered in both of viral and cellular membranes. In order to find the differences between S2 monomer and trimer molecular dynamics, S2 monomer was modelled and subjected to MD simulation. In contrast to S2 trimer, S2 monomer was unstable, having high RMSDs with major drifts above 8 Å. Fluctuation of HR residue positions revealed major changes in the C-terminal of HR2 and the linker coil between HR1 and HR2 in both monomer and trimer. Hydrophobic residues at the a and d positions of HR helices stabilize the whole system, with minimal changes in RMSD. The global distance test and contact area difference scores support instability of MERS CoV S2 monomer. Analysis of HR1-HR2 inter-residue contacts and interaction energy revealed three energy scales along HR helices. Two strong interaction energies were identified at the start of the HR2 helix and at the C-terminal of HR2. The identified critical residues by MD simulation and residues at the a and d positions of HR helix were strong stabilizers of HR recognition.